Peran Agency Theory Terkait Manajemen Risiko Kredit dalam Upaya Meminimalisir Kredit Bermasalah pada KSP Kopdit Obor Mas Kanca Pasar Alok - Chuesta, Rosamunda N. Bella; Sanga, Konstantinus P; Gheta, Antonius P.K (BUDGETING : Journal of Business, Management and Accounting, 2024)
The aim of this research is to determine and analyze the role of agency theory related to credit risk management in efforts minimize problem loans at KSP Kopdit Obor Mas Kanca Pasar Alok. Research data was obtained through direct interviews with Pasar Alok branch managers, observation and documentation. This type of research is descriptive qualitative. The research results show that the analysis of the development of non-performing loans at the Kopdit Obor Mas Kanca Pasar Alok Savings and Loans Cooperative can generally be said to be tending to decline. The increase in non-performing loans from 2019 – 2023. This is caused by an unstable economic situation which ultimately causes people and companies' income to decrease so that customers are in arrears and is also a result of bad character until the time that has been discovered. Keywords: Agency Theory, Cooperatives, Risk Management, Non-Performing Loans